2017
DOI: 10.1371/journal.pone.0180771
|View full text |Cite
|
Sign up to set email alerts
|

Enriched environment and stress exposure influence splenic B lymphocyte composition

Abstract: Prolonged chronic stress has deleterious effects on immune function and is associated with numerous negative health outcomes. The spleen harbors one-fourth of the body’s lymphocytes and mediates both innate and adaptive immune responses. However, the subset of splenic lymphocytes that respond, either adaptively or maladaptively, to various stressors remains largely unknown. Here we investigated the effects of unpredictable chronic mild stress (CMS) exposure on spleen composition in male mice housed in two diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 34 publications
4
20
0
1
Order By: Relevance
“…Interestingly, the sustained upregulation of leukocyte GR into the second generation of offspring may suggest epigenetic adaptation or primordial germline inheritance adaptation. This is also in line with a previous report with upregulated GR in response to chronic mild psychological stress [45]. In the study by Nephew and colleagues, the hypomethylation of GR gene promotor regions was lost in the second-generation offspring.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Interestingly, the sustained upregulation of leukocyte GR into the second generation of offspring may suggest epigenetic adaptation or primordial germline inheritance adaptation. This is also in line with a previous report with upregulated GR in response to chronic mild psychological stress [45]. In the study by Nephew and colleagues, the hypomethylation of GR gene promotor regions was lost in the second-generation offspring.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to current data, splenic macrophages previously displayed insensitivity to glucocorticoids and enhanced IL-6 production in a model of chronic social stress [53]. Although the corticosterone levels were not indicative of glucocorticoid insensitivity in the current study, the modulation of splenic cell composition and GR levels, which was also reported in another model of chronic mild stress [45], suggests a selective GR insensitivity in the splenic macrophages, priming the immune system to a relatively more proinflammatory phenotype.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similarly, a study has recently found that EE during adolescence increased the amount of glucocorticoid receptors in the hippocampus and reduced circulating levels of corticosterone, improving the negative feedback of the neuroendocrine axis in rats from stressed strains (McCreary et al, 2016). At the same time, EE attenuated the increase in corticosterone after alcohol ingestion (Lopez and Laber, 2015) and decreased corticosterone production as measured by fecal corticosterone metabolites in mice (Gurfein et al, 2017). In this context, it is notable that EE influences the neuroendocrine axis and affects the production of glucocorticoids induced by different factors, in agreement with our study.…”
Section: Discussionmentioning
confidence: 87%
“…As a key cell type mediating humoral adaptive immunity, B lymphocytes have rst been described in chickens as antibody-producing cells [22]. Consistent with this essential function, B-lymphocytes development and maturation can be affected by several environmental factors, such as the caging environment [23], heat stress [24], and photoperiod. Here, we constructed a light-color conversion system throughout the growth of chickens to explore the effect of monochromatic lights combinations on Blymphocyte proliferation and bursa development.…”
Section: Effects Of Monochromatic Lights Combinations On B-lymphocytementioning
confidence: 95%